Analisis Minat Investasi Emas Nasabah Bank Syariah Indonesia di Balikpapan - Fransisca Ursula; Wiwin Pebriana; Afrisal Dwi Arianto; Amran Wahyudiah; Nurlia (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the effect of financial literacy, investment risk, and gold price fluctuations on gold investment interest among customers of Bank Syariah Indonesia in Balikpapan. This research used a quantitative approach with an associative research design. The population consisted of 1,200 priority customers, while the sample of 92 respondents was determined using the Slovin formula and selected through convenience sampling. Data were collected through questionnaires distributed directly and via Google Forms using a Likert scale. Data analysis was conducted using Partial Least Square-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results showed that financial literacy, investment risk, and gold price fluctuations have a positive and significant effect on gold investment interest. Financial literacy was found to be the most dominant variable influencing investment interest. The coefficient of determination (R-Square) value of 0.632 indicates that the independent variables explain 63.2% of the variation in gold investment interest, while the remaining 36.8% is influenced by other variables outside the study. This study concludes that improving financial literacy and understanding investment risk can increase customers’ interest in gold investment